Synthesis of Nickel and Nickel Hydroxide Nanopowders by Simplified Chemical Reduction - Jeerapan Tientong; Stephanie Garcia; Casey R. Thurber; Teresa D. Golden (Journal of Nanotechnology)
Nickel nanopowders were synthesized by a chemical reduction of nickel ions with hydrazine hydrate at pH ~12.5. Sonication of the solutions created a temperature of 54–65°C to activate the reduction reaction of nickel nanoparticles. The solution pH affected the composition of the resulting nanoparticles. Nickel hydroxide nanoparticles were formed from an alkaline solution (pH~10) of nickel-hydrazine complexed by dropwise titration. X-ray diffraction of the powder and the analysis of the resulting Williamson-Hall plots revealed that the particle size of the powders ranged from 12 to 14 nm. Addition of polyvinylpyrrolidone into the synthesis decreased the nickel nanoparticle size to approximately 7 nm. Dynamic light scattering and scanning electron microscopy confirmed that the particles were in the nanometer range. The structure of the synthesized nickel and nickel hydroxide nanoparticles was identified by X-ray diffraction and Fourier transform infrared spectroscopy.